Pengaruh Brand Experience dan Online Experience Terhadap Brand Equity Skincare Ms Glow Pada Masyarakat Kota Padang - Putri, Dita Indriani; Rahmidani, Rose (Jurnal Ecogen, 2024)
This research aims to: (1) The influence of Brand Experience and Online Experience on the Brand Equity of Ms Glow Skincare in the people of Padang City. (2) The influence of Brand Experience on the Brand Equity of Ms Glow Skincare in the people of Padang City. (3) The influence of online experience on Brand Equity of Ms Glow Skincare in the people of Padang City. This type of research is causative descriptive research. The population in this research is the people of Padang City. The sample used was 97 people using a non-probability sampling method. The sampling technique is purposive sampling. The type of data in this research is primary data. The data collection technique used is a questionnaire, the data that has been collected is analyzed using descriptive analysis. This research uses Multiple Regression analysis. The research results show that (1) Brand Experience have a significant effect on the Brand Equity of Ms Glow Skincare in the people of Padang City. (2) Online Experience have a significant effect on the Brand Equity of Ms Glow Skincare in the people of Padang City. (3) Brand Experience and Online Experience have a significant effect on the Brand Equity of Ms Glow Skincare in the people of Padang City.